2011
DOI: 10.1136/emermed-2011-200187
|View full text |Cite
|
Sign up to set email alerts
|

Achy breaky makey wakey heart? A randomised crossover trial of musical prompts

Abstract: Listening to DS significantly increased the proportion of prehospital professionals compressing at 2010 guideline-compliant rates. Regardless of intervention more than half gave compressions that were too shallow. Alternative audible feedback mechanisms may be more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 19 publications
(15 reference statements)
0
21
0
3
Order By: Relevance
“…Recent pediatric and adult studies have reported improved resuscitation performance using various auditory prompts and musical tunes. 12,[14][15][16][17][18][19] Commenting on the study by Matlock et al, 15 which used a 105-bpm musical prompt for adult CPR, Rigo and Rigo stated that "newborns need another tune" (Ann Emerg Med. 2009;53:837).…”
Section: Discussionmentioning
confidence: 99%
“…Recent pediatric and adult studies have reported improved resuscitation performance using various auditory prompts and musical tunes. 12,[14][15][16][17][18][19] Commenting on the study by Matlock et al, 15 which used a 105-bpm musical prompt for adult CPR, Rigo and Rigo stated that "newborns need another tune" (Ann Emerg Med. 2009;53:837).…”
Section: Discussionmentioning
confidence: 99%
“…[208][209][210][211]217 One study showed statistically significantly reduced mean compression depth, but this may not be clinically significant (39.3±9.5 mm to 35.8±8.2 mm; P<0.01). 208 Two other studies showed a nonsignificant increase in the proportion of participants unable to perform compressions to adequate depth (OR, 1.23; 95% CI, 0.87-1.74; P=0.24).…”
Section: S256 Circulationmentioning
confidence: 99%
“…208 Two other studies showed a nonsignificant increase in the proportion of participants unable to perform compressions to adequate depth (OR, 1.23; 95% CI, 0.87-1.74; P=0.24). 209,210 Two neonatal studies showed improved compliance with chest compression rates and manual inflation rates, but results were limited to certain pieces of music ("Radetzkymarsch" 211 and ABBA's "SOS" 217 ). For the important outcome of improvement of cognitive knowledge, we found no evidence that examined the use of feedback devices.…”
Section: S256 Circulationmentioning
confidence: 99%
“…All 3 studies found that compression rate was more appropriate when auditory guidance was used, although there was a negative impact on compression depth in 1 study. [94][95][96] If feedback devices are not available, auditory guidance (eg, metronome, music) may be considered to improve adherence to recommendations for chest compression rate only (Class IIb, LOE B-R). These recommendations are made, balancing the potential benefit of improved CPR performance with the cost of the use of such devices during training.…”
Section: Cpr Feedback/prompt Devices In Training Eit 648 -New and Updmentioning
confidence: 99%
“…105 A number of additional studies demonstrated better performance of patient tasks, teamwork, and/or leadership behaviors in the immediate postcourse time period up to 1 year after training. [95][96][97][98][99][100][101][102][103][104][105][106] Given very small risk for harm and the potential benefit of team and leadership training, the inclusion of team and leadership training as part of ALS training is reasonable (Class IIa, LOE C-LD).…”
Section: Team and Leadership Training Eit 631 -Updatedmentioning
confidence: 99%